ChemInform Abstract: Bioinspired Construction of a Spirocyclohexadienone Moiety via Sodium Nitrite Catalyzed Aerobic Intramolecular Oxidative Phenol Coupling. Issue 32 (18th July 2013) - Su, Bo; Deng, Meng; Wang, Qingmin
Abstract Resulting spiro compounds can be further transformed by Lewis acid catalyzed rearrangement reactions into phenanthryl ester (III) and (IV) as well as dibenzoazepines (VII) and (X) which are often difficult to obtain.